Immune‐related lncRNA signature delineates an immune‐excluded subtype of liver cancer with unfavorable clinical outcomes. Issue 3 (18th January 2022) - Chen, Yawei; Xi, Leying; Wei, Lihui; Sun, Debin; Zeng, Tianmei
Abstract: Background: Long non‐coding RNAs (lncRNAs) play crucial roles in immune regulation and, therefore, may be closely related to the tumor microenvironment (TME). However, there are few studies regarding the relationship between the lncRNAs and the TME in liver cancer. Methods: Firstly, we constructed a lncRNA signature based on the top 10 immune‐inversely related lncRNAs obtained from the ImmLnc database and performed disease‐free survival (DFS) and overall survival (OS) analyses for the patients included in the Cancer Genome Atlas Liver Hepatocellular Carcinoma (TCGA‐LIHC) stratified by the lncRNA signature. Then, we explored the relationship between the lncRNA signature with distinct mutation profiles and the tumor microenvironment (TME). Results: The lncRNA signature was successfully constructed and verified by survival analysis. The high lncRNA signature was correlated with a decreased DFS and OS in liver cancer and other two gastrointestinal cancers. The mutation profiles showed that the Lnc_high group had a higher number of mutations on many genes, mostly enriched in p53 and WNT pathways. The TME results showed that the Lnc_high group had the highest proportion (51%) of lymphocyte depletion‐characterized immune subtype, and a higher expression of immune checkpoint molecules such as LAG3, PD‐L1, CTLA4. On the contrary, in the Lnc_low group, infiltrating immune‐cell proportions were significantly higher, and a significant enhancement of four axes of the cancer immunity cycle immunogram was observed in this group. Conclusions: The lncRNA signature we constructed identified an immune‐excluded subtype of liver cancer with unfavorable clinic outcomes, which could be tested as a biomarker for immunotherapy in the future. Abstract : We constructed a novel immune‐related lncRNA signature based on lncRNAs that affect immune pathway activity and determined that this lncRNA signature correlated with the progression and prognosis of liver cancer. The lncRNA signature had a significant relationship with tumor mutations and the TME and may be integrated into a comprehensive biomarker system for liver cancer immunotherapy.